Feasibility of Bridge Deicing Using Geothermal Energy Piles in Different U.S. Climates. Issue 9 (September 2022) - Xiao, Suguang; Suleiman, Muhannad T.; Sudhakar, Neti; Naito, Clay J.; Zhang, Guozhu
Geothermal energy piles are an environmentally friendly energy source and an innovative approach to melt snow on the bridge surface and minimize or eliminate the use of deicing salt. However, the application potential of energy piles for bridge deicing or snow melting has not been fully explored for different climates. In this study, the feasibility of using energy piles for bridge deicing in eight cities of the United States was investigated. Temperature response function (G function) method was validated and used to estimate the extracted heat from energy piles installed in the soils with different thermal properties, which was used to heat the bridge deck during snowing. The results of numerical simulation and statistical analysis confirm that the performance of the geothermal deicing system depends on the weather conditions during snowing and thermal properties of soils. The coverage rate of the geothermal system (percentage of snowing time that the geothermal deicing system can keep the bridge surface above 0°C) increases with the increasing air temperature and thermal diffusivities of soils, and decreases with the increasing precipitation rate and wind speed. This deicing method is promising in cities with higher average air temperature and low precipitation rate during snowing.